Horia Lovinescu, Between the “Terror of History” and Psychoanalytical Dreams - POP-CURȘEU, Ioan (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
This paper focuses on Horia Lovinescu (1917-1983), a member of one of the most important dynasties of modern Romanian culture. Six of Horia Lovinescu’s dramas are interpreted in a close reading system, by psychoanalytical tools and by focusing on the family constellations the author imagines. These plays are related to the historical context (“the terror of history”), in order to understand how works of art are the reverberation of biographical-creative data of the greatest importance and how they echo in a paradoxical way social-political transformations. This double reading, psychological and historical, is justified by the playwright himself, through the construction of his plays and through his many allusions to psychoanalysis in his writings.